Bentuk Distribusi dan Rata-Rata Pendapatan Apotek Gracia Farma Sebelum dan Saat Covid-19 - Frederikus Seran; Aloisius Loka Son; Eva Binsasi (Program Studi Matematika, Universitas Timor, 2025)
This research was carried out because of the emergence of the corona virus in Wuhan, China in December 2019. This virus has had many impacts, one of which is the amount of income in micro and macro businesses. The aim of this research is to determine the form of distribution and average income of the Gracia Farma Pharmacy before Covid-19 and during Covid-19. This research was carried out at the Gracia Farma Pharmacy, Kefamenanu City, North Central Timor Regency from 1 November 2019 to 31 August 2020. The data processing technique in this research was preceded by Distribution Fitting and parameter estimation using the Maximum Loglikehood Estimation (MLE) method, then model selection was carried out. The best method is using Akaike's Information Criterion (AIC) and Bayesian Information Criterion (BIC). The results of this research show that the form of distribution that corresponds to the total income data before Covid-19 is a Normal distribution with an average income of IDR 306,832 and the form of distribution that corresponds to the amount of income during Covid-19 is a Normal distribution with an average income Rp. 332,050.